Dielectrics: Mechanical and Electric Control of Photonic Modes in Random Dielectrics (Adv. Mater. 12/2019). Issue 12 (19th March 2019) - Balestri, Dario; Petruzzella, Maurangelo; Checcucci, Simona; Intonti, Francesca; Caselli, Niccolò; Sgrignuoli, Fabrizio; van Otten, Frank W. M.; Fiore, Andrea; Gurioli, Massimo
Abstract : Double‐membrane disordered dielectric devices with embedded quantum dots allow reversible and large spectral tuning of localized random photonic modes at telecom wavelengths with mechanical and electric techniques. The tuning of hundreds of modes per device, sparse over a large spectral range, is achieved by Dario Balestri and co‐workers in article number1807274 without changing the mode spatial distribution, thus addressing the request needed for the matching with an emitter.